Modeling of Phosphorus Nutrition to Obtain Maximum Yield, High P Use Efficiency and Low P-Loss Risk for Wheat Grown in Sandy Calcareous Soils - Zhanyao Hu; Zheli Ding; Hatim M. Al-Yasi; Esmat F. Ali; Mamdouh A. Eissa; Salah F. Abou-Elwafa; Mohammed Abdelaziz Sayed; Mohamed Tharwat Said; Alaa A. Said; Khaled A. M. Ibrahim; Alhosein Hamada (Agronomy, 2021)
Fertilization with high levels of phosphorus increases the risk of environmental pollution. Identification of critical values of P in soil (SOP) and in plant tissues (PiP) is essential for achieving the maximum wheat yield without P loss. The critical value is the value of P which gives the optimum yield; the response of crop yield to P fertilization above this value is not predictable or nil. Here, a 4-year field experiment was conducted to identify the SOP and PiP for achieving maximum yield of bread wheat using 11 rates of P fertilization (0, 15, 30, 45, 60, 75, 90, 105, 120, 135, and 150 kg P2O5 ha−1). The linear–linear and Mitscherlich exponential models were employed to estimate the PiP and SOP. The degree of phosphorus saturation (DPS) was used to assess the potential environmental risk; furthermore, phosphorus use efficiency (PUE) was also calculated under the studied fertilization levels. Phosphorus in soil and wheat plant was affected by the application rates and growing seasons. Increasing P fertilization rates led to gradual increases in soil and plant P. The SOP ranged between 21 and 32 mg kg−1, while the PiP ranged between 6.40 and 7.49 g kg−1. The critical values of P calculated from the Mitscherlich exponential models were 20% higher than those calculated from the linear–linear models. Adding levels of P fertilization ≥90 kg P2O5 ha−1 leads to higher potentials of P runoff and leaching, in addition, PUE decreased sharply under high P fertilization levels. The response of wheat yield to P fertilization in sandy calcareous soil is predictable below Olsen P values of 21 mg kg−1. Identification of critical P values for wheat production is of great importance to help policy makers improve P use efficiency and attain optimum wheat yield under eco-friendly environmental conditions by eliminating the accumulation of excess P fertilizers in soil and water.